Vtisi ob jubileju testiranja za športnovzgojni karton na Osnovni šoli Žiri - Poljanšek, Adelina (Šport (Ljubljana), 2017)
The Sports Educational Chart or SLOfit is a national system for monitoring of children's and adolescents' physical and motor development in which all Slovenian primary and secondary schools take part, including the Žiri Primary School. The Žiri Primary School is aware of the fact that our results are always above the Slovenian average, and in the last decade we have usually ranked among the top 5 % of performers and at the bottom according to body height and weight. Evaluation of physical fitness is important to us, teachers, especially for the purpose of planning of our work. A comparison of physical development of our children in the 1990-2017 period shows that children are currently 4 cm taller, 4 kg heavier by and have 2 mm less subcutaneous fat; the body height of female pupils has not changed, whereas they are 2 kg heavier and have 3 mm less subcutaneous fat, which means they have more muscle mass. A comparison of their physical development shows that boys have progressed by 12 % in this period and girls by 6 %, on average. The members of our school staff believe that these positive trends are a result of the combination of promoting sport in school, the natural environment around the town, the promotion of sports activities at the local level, the diligence of the local people, Žiri's group of sports experts, who have helped build a sporting atmosphere in the town for decades, as well as Žiri's townspeople who have high sports awareness.
Keywords: adolescents; children; health; mladina; osnovna šola; otroci; physical activity; physical fitness; primary school; SLOfit; sport; šport; športna vzgoja; športnovzgojni karton; telesna dejavnost; telesni fitnes; zdravje